Moral Policing and Gender-based Violence: Portrayal of Honour and Shame in Poile Sengupta’s Mangalam - Singh, Bhawna; Hameed, Ansa; Alam, Sohaib (Journal of Education Culture and Society, 2023)
Thesis. The article aims to study Poile Sengupta’s play entitled Mangalam to analyse how the play raises a voice against society’s enforced models of masculinity and femininity, and sexual and psychological violence and its impact on women in the domestic sphere. Concept. The study foregrounds the impact of moral policing via the notions of honour and shame in Sengupta’s Mangalam and analyses that family, a micro-unit of patriarchy is the primary location of violence inflicted on women. The present study further attempts to examine interpersonal violence perpetuated through the institution of marriage through a study of the portrayal of marital violence in Sengupta’s Mangalam. Results and Conclusion. Sengupta presents contemporary social issues and interrogates moral policing and violence perpetuated by patriarchy through the discussed play. It presents a dramatic piece written by a woman, thus challenging the male-dominated narratives through a voice of protest and addressing violence inflicted on a woman’s body and psyche. Originality. The originality of the study relies on examining the underlying causes of gender-based violence within the institution of marriage and family as the smallest unit of patriarchy while also understanding the relevance of literary representations by women dramatists as resistance literature.